The Signification (Referent) of the Qur'an in the Process of Presenting Hadith; Based on the Application of the Supply Criterion (Standard) by the Infallibles (Maʿṣūmīn) (p.b.u.t.) - Ahmad Jamali Gandomani; Muhammad Kazem Rahman Setayesh (آموزه‌های قرآنی)
Forgery (invention) of hadith, error and mistake of some narrators in hearing, understanding or quoting hadith indicates the necessity of criticizing narrations to ensure their correctness or incorrectness. To deal with these harms, the most frequent advice of the infallibles (p.b.u.t.) is to criticize the content with the focus on presenting the hadith on the Qur'an. However, despite exploring the nature (quiddity) and validity of the narrations of presentation, related to the signification (referent) of the Qur'an in the process of presentation has not been studied based on the applications of this criterion (standard) by the Imams (p.b.u.t.) and focusing on the hadith view. This research has analyzed the text of the narrations of the presentation and the example of the narrations presented on the Qur'an by the Imams (p.b.u.t.) by descriptive-analytical method with the aim of investigating this issue. According to the narrative examples of presentation, the signification (referent) of the Qur'an in the process of presentation is a model consisting of at least one of the text, appearance (exoteric), principles, discourse and esoteric interpretative signification (referent) of the Qur'an (on this condition that does not contradict other significations). Quranic principles in this research are fixed and what is meant by the discourse of the Qur'an is a set of institutionalized teachings of the Qur'an on various subjects, from which the concept in question may not be understood separately, but together they convey a special meaning to the reader.